Elementary School Students' Waste Management Behavior Determinant in Kerinci Regency in 2021 - Hubaybah Hubaybah; Fuji Arinda Fitri; Oka Lesmana; Fajrina Hidayati; Puspita Sari (International Journal Of Health Science, 2022)
The existence of waste at this time was still a problem that hit almost all regions in Indonesia. Keliling Danau Districts in 2019 has produces 33,311 m3 of waste per year with a population of 22,207 people. The purpose of this study was to determine the determinants behavior of waste management in elementary school students at Kerinci Regency, 2021. This study aims to determine the relationship between knowledge, attitudes, and Availability of Facilities with Waste Management in State Elementary School 52 of Koto Dian students, Kerinci Regency. This research is quantitative with a cross sectional research design. Sampling using random sampling technique with a total sample of 44 students consisted of class III, IV, V to class VI. Data was collected by distributed of questionnaires. Analysis used chi-square test. The results of this study indicate that 18 of 44 (40.9%) respondents with poor behavior of waste management and 26 (59.1%) respondents with good behavior waste management. From the results of the bivariate test, it was found that Knowledge has a PR value = 3.33 CI = 1.73-6.39 and a p-value of 0.001 indicates that there is a relationship between knowledge and behavior of waste management. Attitude has a value of PR = 3.75 CI = 1.62-8.68 and a p-value of 0.001 indicates that there was a relationship between attitude and behavior of waste management and there was not relationship between availability of facilities and behavior of waste management with a p-value of 0.222. The conclusion of this study is that there is a relationship between knowledge and attitudes with behavior waste management. And the availability of facilities has no relationship between behavior of waste management in elementary school students.